PRIORITAS PEMELIHARAAN JALAN BERBASIS TREATMENT PRIORITY INDEX (TPI) DI JALAN PERKERASAN ASPAL - Pangesti, Rendy Dwi; Sulistiawati, Baiq Heny; Wahyono, Herry Ludiro; Junaidi, Junaidi; Goro, Garup Lambang (Politeknik Negeri Semarang, 2024)
The increase in the number of vehicles and economic growth in the city of Semarang puts significant pressure on road infrastructure. So it is necessary to prioritize maintenance on several road sections. This research uses the Treatment Priority Index (TPI) approach to identify road repair priorities in Tembalang District, Semarang City. Data on road conditions and daily traffic volume are variables in the TPI analysis and the data is analyzed using the Provincial District Road Management System (PKRMS). The results of the TPI analysis obtained road sections with critical conditions, especially Telumpak (TPI: 26.2) and Salak (TPI: 25.7). These sections require immediate repairs to ensure the safety and comfort of road users. This research provides a basis for information for policy makers to allocate resources efficiently, ensure sustainable road infrastructure, and support effective mobility in Semarang City, especially in Tembalang District.